Diagnostic and Prognostic Utility of Circulating Cytochrome c in Acute Myocardial Infarction. Issue 12 (9th December 2016) - Marenzi, Giancarlo; Cosentino, Nicola; Boeddinghaus, Jasper; Trinei, Mirella; Giorgio, Marco; Milazzo, Valentina; Moltrasio, Marco; Cardinale, Daniela; Sandri, Maria Teresa; Veglia, Fabrizio; Bonomi, Alice; Kaech, Max; et al.
Abstract : Rationale: : In contrast to cardiomyocyte necrosis, which can be quantified by cardiac troponin, functional cardiomyocyte impairment, including mitochondrial dysfunction, has escaped clinical recognition in acute myocardial infarction (AMI) patients. Objective: : To investigate the diagnostic accuracy for AMI and prognostic prediction of in-hospital mortality of cytochrome c . Methods and Results: : We prospectively assessed cytochrome c serum levels at hospital presentation in 2 cohorts: a diagnostic cohort of patients presenting with suspected AMI and a prognostic cohort of definite AMI patients. Diagnostic accuracy for AMI was the primary diagnostic end point, and prognostic prediction of in-hospital mortality was the primary prognostic end point. Serum cytochrome c had no diagnostic utility for AMI (area under the receiver-operating characteristics curve 0.51; 95% confidence intervals 0.44–0.58; P =0.76). Among 753 AMI patients in the prognostic cohort, cytochrome c was detectable in 280 (37%) patients. These patients had higher in-hospital mortality than patients with nondetectable cytochrome c (6% versus 1%; P <0.001). This result was mainly driven by the high mortality rate observed in ST-segment–elevation AMI patients with detectable cytochrome c, as compared with those with nondetectable cytochrome c (11% versus 1%; P <0.001). At multivariable analysis, cytochrome c remained a significant independent predictor of in-hospital mortality (odds ratio 3.0; 95% confidence interval 1.9–5.7; P <0.001), even after adjustment for major clinical confounders (odds ratio 4.01; 95% confidence interval 1.20–13.38; P =0.02). Conclusions: : Cytochrome c serum concentrations do not have diagnostic but substantial prognostic utility in AMI. Abstract : Supplemental Digital Content is available in the text.